Microplastics in food products: Prevalence, artificial intelligence based detection, and potential health impacts on humans - M. Amin Mir; Muhammad Azhar Ali Khan; Bimal Krishna Banik; Syed M. Hasnain; Lina Alzayer; K. Andrews; Sani I. Abba (Emerging Contaminants)
Microplastic contamination in food products has become a growing concern due to its potential implications for human health, the environment, and food safety. Over the past decade, microplastics have been detected in a wide variety of food items, including seafood, salt, processed foods, and beverages. This review provides a comprehensive description of the sources, detection methods, and health risks associated with microplastics in food. The contamination pathways, including inhalation, and dermal contact, are discussed, with a focus on the most common exposure route—ingestion through contaminated food and water. Among the health hazards that microplastics present include oxidative stress, immune system disturbance, neurotoxicity, reproductive toxicity, and possible carcinogenic consequences. Concerns about nanoplastics' toxicity are heightened by their capacity to cross biological barriers and build up in tissues. The research also highlights the necessity of better detection methods, like multispectral imaging and AI-based algorithms, to increase the precision and effectiveness of microplastic identification in food. It also talks about how crucial it is to comprehend the origins and routes of contamination in order to lessen the impact of microplastics in the food supply chain. Critical future research directions are outlined including the creation of regulatory frameworks to restrict exposure to microplastics, standardized detection techniques, and longitudinal human health studies. The evaluation also highlights the need for comprehensive measures to combat microplastic contamination in food by promoting public awareness campaigns and the creation of sustainable alternatives to plastic packaging.